A Naturalistic Study Design of the Warm-Up Prompt and Online Planning Effect on Fluency in Informal Dialogues - Hanafi Hanafi (JET ADI BUANA, 2022)
As many studies on pre-task planning and a few on online planning were designed in experimental settings, this research article offers a naturalistic model for investigating the effect of warm-up prompt and online planning effect on fluency in informal dialogues. Among Skehan’s (1996) three parameters of oral language performance, the researcher focused only on measuring the fluency of two male Indonesian learners of English as a Second Language. The participants were also explicitly prepared for the topic through preconditioning information and warm-up prompts. They were also implicitly allowed to have ‘rapid planning’ (Ochs, 1979) or online planning strategy in response to the questions. Their entire informal conversations were audio-taped, transcribed, and analyzed according to Ellis and Barkhuizen’s (2005) scheme of measuring spoken language. The result shows that participants of different proficiencies committed errors of fluency by choice as their online planning strategy. However, the high proficient learner produced fewer errors that the low proficient learner did. They both used the errors for making rapid / online planning to buy time but for two different purposes. The high proficient speaker planned for strategic purposes and formulating a better answer while the low proficient speaker planned mostly for overcoming shortage of vocabularies. The errors were also found to be used in combined format thereby giving the full time-buying benefit for the speakers in their online planning mode.